Study of improving the customer relationship management by data mining applications - Danubianu, Mirela; Stanica, Anca Maria (Оптико-електронні інформаційно-енергетичні технології, 2009)
Companies must survive in a market, where are a lot of products and competitors which compete to gain the customers. In a such market there are some factors which influences the growing of the complexity of customer relationships. Some of these factors are: the compression of the marketing cycle times, the increasing of marketing costs, the avalanche of new products offering and the existence of niche competitors. The companies must react quickly to the challenges of these factors, reaction which consist in the right offer to the right person at the right time trough the right channel. CRM involves new ways of interacting with the customers which promises higher returns on investments for businesses by enhancing customer-oriented processes such as sales, marketing, and customer service. Data mining- techniques for automate detecting of relevant patterns in databases- helps companies build personal and profitable customer relationships by identifying and anticipating the needs of customers throughout the customer lifecycle.